Comparison of pre- and intra-COVID-19 postpartum depression among reproductive aged women: A comparative cross-sectional study in Ahvaz, Iran - Afshari, Poorandokht; Tadayon, Mitra; Abedi, Parvin; Beheshtinasab, Maryam (Frontiers in Psychiatry, 2022)
Background The association between PPD and COVID-19 pandemic has been studied in some countries. This study aimed to compare postpartum depression before and during the COVID-19 pandemic among reproductive-aged women in Ahvaz, Iran. Methods This comparative cross-sectional study involved 600 women of reproductive age in Ahvaz, Iran during the COVID-19 pandemic who were compared with 504 of their counterparts before the pandemic. Literate women who had given birth 1–6 months prior to the study, were aged 18–35, and were willing to participate in this study were recruited. A demographic questionnaire and Edinburgh Postnatal Depression Scale were used to collect the data. Independent t-test, Chi-square, and Logistic regression were used to analyze the data. Results Before the pandemic, only 123 (24.9%) of the women had PPD, while during the pandemic, this number rose to 409 (68.2%). During the COVID-19 pandemic, the women were 8.727 times more likely to have PPD (95% CI: 5.919–12.868). During the pandemic, women with high school education and those having a high school diploma were 2.454 and 2.054 times more likely to have PPD compared to women with a university degree (95% CI: 1.508–3.996 and 1.302–3.241, respectively). Conclusion The prevalence of PPD among Iranian reproductive-aged women increased during the COVID-19 pandemic. Policymakers should seek some strategies to support women during pregnancy and postpartum in times of crises such as the COVID-19 pandemic.